Cluster‐Glass for Low‐Cost White‐Light Emission. Issue 33 (14th July 2022) - Rojas‐León, Irán; Christmann, Jan; Schwan, Sebastian; Ziese, Ferdinand; Sanna, Simone; Mollenhauer, Doreen; Rosemann, Nils W.; Dehnen, Stefanie
Abstract: The development of efficient and high‐brilliance white‐light sources is an essential contribution to innovative emission technologies. Materials exhibiting strong nonlinear optical properties, in particular second‐harmonic generation (SHG) or white‐light generation (WLG), have therefore been investigated with great activity in recent times. While many new approaches have been reported until now, the processability of the compounds remains a challenge. Here, a new class of materials, denoted as "cluster‐glass", which do not only show superior white‐light emission properties upon irradiation by an inexpensive continuous‐wave infrared laser diode, but can be easily accommodated in size and shape by formation of robust glassy solids, is introduced. The cluster‐glass materials are fabricated by mild heating from crystalline powders of adamantane‐type clusters exhibiting a quaternary, inorganic–organic hybrid cluster core [(PhSi)(CH2 )3 (PhSn)E3 ] (E  =  S, Se, Te). The process is fully reversible and preserves the integrity of the clusters in the glass, as proven by solution spectroscopy and recrystallization. Theoretical studies corroborate the importance of the quaternary nature of the cluster cores for the observed structural and optical phenomena. Thanks to these findings, high‐brilliance white‐light sources can be synthesized in form of stable, robust glass of any shape, which ultimately renders them suitable for everyday's applications. Abstract : A new class of amorphous molecular materials for white‐light generation (WLG) by means of continuous‐wave infrared lasers is introduced, denoted as "cluster‐glass". For their fabrication, compounds of the general formula [(PhSi)(CH2 )3 (PhSn)E3 ] (E = S, Se, Te) are synthesized in pure and crystalline form and reversibly transformed into amorphous, robust glasses of any shape by mild heating. The materials and WLG properties of the cluster‐glasses are studied by a combined experimental and quantum chemical study.